Milk thistle (Silybum marianum) as a Promising Chemoprotective Agent for Liver Therapy - Iqbal, Muhammad Naeem; Ashraf, Asfa (PSM Biological Research, 2020)
There is a great interest in combining anticancer drugs with natural products aiming at maximizing their efficacy while minimizing systemic toxicity. Milk thistle (Silybum marianum) was used against chemotherapy-induced organ toxicity. Screening for natural substances with chemopreventive properties in order to reduce the negative effects of chemotherapeutic drugs is very urgent. It has been demonstrated that milk thistle extract could act as a promising chemoprotective agent for liver therapy to avoid side effects.